Parenting children with disabilities in Sweden: a cluster-analysis of parenting stress and sufficiency of informal and formal support - Täljedal, Torun; Granlund, Mats; Osman, Fatumo; Norén Selinus, Eva; Fängström, Karin (Frontiers in Psychology, 2024)
Objective. To investigate patterns of parenting stress and access to sufficient informal and formal support among parents of children with disabilities. To explore whether child cognitive level, conduct problems and the need of language interpretation in contacts between parents and professionals are associated with patterns of parenting stress and support.Method. Parents (N=140) of children with disabilities in Sweden completed a questionnaire about parenting stress and support. Patterns of three variables -parenting stress and access to sufficient informal and formal support -were investigated using cluster analysis. The relationship of child cognitive level, level of conduct problems and of language interpretation needs between parents and professionals to cluster membership was explored using multinomial logistic regression.Results. Five different clusters of parenting stress and support emerged. Parents in cluster 1 had lower than sample mean ratings on all three variables. Cluster 2 had elevated parenting stress, cluster 3 had elevated insufficient informal support and cluster 4 had elevated insufficient formal support. Cluster 5 had elevated ratings on all three variables. Greater child cognitive difficulties increased the likelihood of parent membership in cluster 2 (elevated stress), cluster 3 (elevated insufficient informal support) or cluster 5 (elevated ratings on all variables). Child conduct problems increased the likelihood of membership in cluster 2 (elevated stress) or cluster 5 (elevated ratings on all variables). No relationship between language interpretation needs and cluster membership was found.Conclusions. Patterns of parenting stress and sufficiency of support, and their associations with child characteristics, vary substantially. However, families of children with conduct problems experiencing elevated parenting stress in combination with insufficient informal and formal support, may be particularly vulnerable. The results of the current study highlight the clinical importance of exploring and identifying individual parenting stressors and perceived levels of support, to be able to adapt services to better suit a variety of needs, and thus promote equitable care.